EKSISTENSI KEPONGOR DI BALI REFLEKSI TERHADAP AJARAN KARMAPHALA - I Nyoman Suharko; I Gede Suwantana; Ni Luh Gede Wariati (Pangkaja: Jurnal Agama Hindu, 2021)
Kepongor for the Hindu community in Bali is a belief (belief) based on a tradition and ancestral culture. Where the kepongor culture is a form of teaching about human behavior (deeds), ethics and morality which is applied from generation to generation through a curse, it is possible that all descendants are always aware of (remember) the ancestors. Religion is taught and socialized to humans based on the text of the Veda scriptures, lontar, and Bisama (warning) from generation to generation. This has served to provide a belief about how diversity and culture are carried out by humans based on the Five Sradha and Tri Hindu religious frameworks, tattwa, morals and events. On the basis of sradha and bahakti, things that are beyond human reason and logic that are abstract in nature which cause sorrow, pain, etc. can be avoided. Through the description above, the problems discussed in this study include: 1) the form of kepongor experienced by Balinese, 2) Balinese people can learn and overcome kepongor, 3) the implementation of karmaphala teachings on the incidence of kepongor